Hypothalamic TTF-1 orchestrates the sensitivity of leptin - Byong Seo Park; Dasol Kang; Kwang Kon Kim; Bora Jeong; Tae Hwan Lee; Jeong Woo Park; Shioko Kimura; Jung-Yong Yeh; Gu Seob Roh; Chang-Joong Lee; Sungchil Yang; Sunggu Yang; et al. (Molecular Metabolism, 2022)
Objective: Thyroid transcription factor-1 (TTF-1), a homeodomain-containing transcription factor, is predominantly expressed in discrete areas of the hypothalamus, which acts as the central unit for the regulation of whole-body energy homeostasis. Current study designed to identify the roles of TTF-1 on the responsiveness of the hypothalamic circuit activity to circulating leptin and the development of obesity linked to the insensitivity of leptin. Methods: We generated conditional knock-out mice by crossing TTF-1flox/flox mice with leptin receptor (ObRb)Cre or proopiomelanocortin (POMC)Cre transgenic mice to interrogate the contributions of TTF-1 in leptin signaling and activity. Changes of food intake, body weight and energy expenditure were evaluated in standard or high fat diet-treated transgenic mice by using an indirect calorimetry instrument. Molecular mechanism was elucidated with immunohistochemistry, immunoblotting, quantitative PCR, and promoter assays. Results: The selective deletion of TTF-1 gene expression in cells expressing the ObRb or POMC enhanced the anorexigenic effects of leptin as well as the leptin-induced phosphorylation of STAT3. We further determined that TTF-1 inhibited the transcriptional activity of the ObRb gene. In line with these findings, the selective deletion of the TTF-1 gene in ObRb-positive cells led to protective effects against diet-induced obesity via the amelioration of leptin resistance. Conclusions: Collectively, these results suggest that hypothalamic TTF-1 participates in the development of obesity as a molecular component involved in the regulation of cellular leptin signaling and activity. Thus, TTF-1 may represent a therapeutic target for the treatment, prevention, and control of obesity.